2002
DOI: 10.1111/j.1748-0361.2002.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Rural AIDS Epidemiology and Service Delivery Models in the United States

Abstract: This article reviews AIDS surveillance data and the rural health literature to summarize what is known about the rural AIDS epidemic, characteristics of rural environments that affect HIV service delivery, and approaches that rural areas are using to address the health and support service needs of HIV-positive residents. During 1999, nonmetropolitan (non-MSA) adult/adolescent AIDS rates were highest in the South (11 per 100,000) and Northeast (9 per 100,000). The South had the highest non-MSA proportion of adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…This number more than doubled to 45,643 by the year 2000 (McKinney, 2002). The South accounted for more than two-thirds of non-MSA AIDS cases in 2001, with non-MSA Southerners accounting for 21% of the regions incident HIV-diagnoses (CDC, unpublished data).…”
Section: Rural Residencementioning
confidence: 99%
See 2 more Smart Citations
“…This number more than doubled to 45,643 by the year 2000 (McKinney, 2002). The South accounted for more than two-thirds of non-MSA AIDS cases in 2001, with non-MSA Southerners accounting for 21% of the regions incident HIV-diagnoses (CDC, unpublished data).…”
Section: Rural Residencementioning
confidence: 99%
“…At the UAB 1917 Clinic, 25.8% of patients were from Alabama non-MSA, and 43.3% of these patients already had CDC-defined AIDS at first presentation (Krawczyk et al, 2006). A higher proportion of HIV-infected rural residents are uninsured (19.6%) or publicly insured (13.4%) when compared to urban residents (14.3% and 11.1%, respectively) (McKinney 2002). The adverse impact of uninsured status among rural HIV-infected Southerners is clear; in a survey of non-urban HIV-infected Alabamians, 39% had no form of insurance and 16% had lost their insurance since becoming HIV-infected (Beltrami et al, 1999).…”
Section: Rural Residencementioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition, rural regions in particular are affected by inadequate health infrastructure, underfunded rural health and social services programs, higher poverty, geographic challenges and a higher proportion of people who lack health insurance. 13,[21][22][23] The handful of HIV-related stigma and discrimination studies conducted in rural areas suggests that social context matters. In a study comparing urban and rural people living with HIV=AIDS, Heckman et al 24 found that rural people living with HIV, compared to their urban counterparts, reported significantly lower satisfaction with life, lower perceptions of social support from family members and friends, reduced access to medical and mental health care, elevated levels of loneliness, more community stigma, and heightened personal fear.…”
mentioning
confidence: 99%
“…8 Other research indicates that people living with HIV in rural areas travel to metropolitan areas for medical care due to concerns about confidentiality, or lack of confidence in the ability of rural physicians to assist in the medical management of HIV infection. 9 Researchers have also reported that rural residents living with HIV are challenged by a lack of adequately trained medical and mental health providers. 8 It has been recognized for quite some time that certain illnesses or conditions are associated with an increased level of stigma, 10 including: lung cancer, 11 sexually transmitted infections, 12 and HIV/AIDS.…”
mentioning
confidence: 99%